Kajian Tingkat Kontinum Kapital Sosial Fakultas Tarbiyah dan Keguruan dan mewujudkan visi dan misi dan tujuan UIN Sultan Syarif Kasim Riau - Ansharullah Ansharullah (Lembaga penelitian dan pengabdian kepada Masyarakat, 2013)
affect the level of social capital owned continuum employee and lecturer in the Faculty of Educatuion and Teaching Of State Islamic university of Suska Riau. The subjects were employees and lecturer in the Faculty of Of State Islamic university of Suska Riau. While the object of this study is the level of social capital owned continuum employee and lecturer in the Faculty of Educatuion and Teaching Of State Islamic university of Suska Riau. The study population was all employees structural (administration) and functional as many as 44 people (lecturers) as many as 158 people. The sampling method consisted of two ways, namely for employees structural variables using total sampling method and for the functional variables (lecturer) using purposive indicate that the level of social capital continuum structurally categories and cognitive categories that are owned by the employee and lecturer at the Faculty of Educatuion and Teaching of State Islamic university of capital category with a percentage of 79.90%, as it ranges between 76% - 100%.